1990
DOI: 10.1097/00004032-199005000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of 129I in Human and Bovine Thyroids in Europe-transfer of 129I Into the Food Chain

Abstract: Bovine thyroid glands from different countries in Europe and human thyroid glands from Lower Saxony (Federal Republic of Germany) show isotopic 129I/127I ratios of 2.1 X 10(-9) to 8.2 X 10(-8) for cattle and 2.1 X 10(-9) to 8 X 10(-8) in humans. These values give information about the concentration of fallout 129I in Europe since most of these glands were collected in areas without nuclear facilities. Some of the human thyroids were collected after the Chernobyl accident between May 1986 and February 1988. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The review by Bishop et al (1989) reports a value of 3.6 Â 10 À3 d kg À1 given by Ng et al (1982) which is similar to the value in Table 5 and is an estimate derived from a USA reference (NAS-NRC, 1963). Other relevant values are reported by Hauschild and Aumann (1989) of 3.9 Â 10 À3 d kg À1 -1.1 Â10 À2 d kg À1 , Handl et al (1990) of 3.8 Â 10 À2 d kg À1 (summarising data in Handl and Pfau, 1989) and Bonka et al (1988) of 2 Â 10 À3 d kg À1 which are also similar to the Sirotkin value; these four data sources provide the revised IAEA value of 6.7 Â 10 À3 d kg À1 (Howard et al, submitted for publication).…”
Section: Iodinementioning
confidence: 97%
“…The review by Bishop et al (1989) reports a value of 3.6 Â 10 À3 d kg À1 given by Ng et al (1982) which is similar to the value in Table 5 and is an estimate derived from a USA reference (NAS-NRC, 1963). Other relevant values are reported by Hauschild and Aumann (1989) of 3.9 Â 10 À3 d kg À1 -1.1 Â10 À2 d kg À1 , Handl et al (1990) of 3.8 Â 10 À2 d kg À1 (summarising data in Handl and Pfau, 1989) and Bonka et al (1988) of 2 Â 10 À3 d kg À1 which are also similar to the Sirotkin value; these four data sources provide the revised IAEA value of 6.7 Â 10 À3 d kg À1 (Howard et al, submitted for publication).…”
Section: Iodinementioning
confidence: 97%
“…In Europe, during 1981 the 129 I/ 127 I in 22 bovine thyroids was measured by HANDL et al 6 Their results showed the background ratio in Germany at that time was 4.7 . 10 9 .…”
Section: Measurementmentioning
confidence: 98%
“…One reason may relate to the long half-life (15.7 million years) of the isotope that makes it a low-radioactive risk. Some studies have, however, indicated an enhanced accumulation of the isotope in animal and human organs (Handl et al, 1990;Handl, 1996;Hou et al, 2000Hou et al, , 2003aFréchou et al, 2002), which call for a more comprehensive evaluation of the impact of 129 I on the environment and human health.…”
Section: Environmental Impactmentioning
confidence: 99%